2018
DOI: 10.3389/fphys.2018.00288
|View full text |Cite
|
Sign up to set email alerts
|

Dendritic Cell Migration Toward CCL21 Gradient Requires Functional Cx43

Abstract: Dendritic cells (DCs) travel through lymphatic vessels to transport antigens and present them to T cells in lymph nodes. DCs move directionally toward lymphatics by virtue of their CCR7 and a CCL21 chemotactic gradient. We evaluated in vivo and in bone marrow-derived dendritic cells (BMDCs) whether the gap junction protein Cx43 contributes to CCL21/CCR7-dependent DC migration in wild-type (WT) mice, heterozygous (Cx43+/−) mice and mice expressing a truncated form of Cx43 lacking its regulatory C-terminus (Cx43… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
0
13
0
1
Order By: Relevance
“…In vitro studies using bone marrow-derived DCs (BMDCs) from mice with reduced Cx43 expression revealed defective migration towards CCL21. Moreover, reduced cDC migration to the lymph node in vivo was observed in mice expressing a truncated form of Cx43 [98]. Although there was no direct connection defined between Cx43 and the directional movement of DCs, it has previously been noted that connexin interacts with c-Src kinase involved in CCL21-directed movement [97][98][99].…”
Section: Directional Migration Of Dendritic Cells Towards Lymphaticsmentioning
confidence: 97%
See 2 more Smart Citations
“…In vitro studies using bone marrow-derived DCs (BMDCs) from mice with reduced Cx43 expression revealed defective migration towards CCL21. Moreover, reduced cDC migration to the lymph node in vivo was observed in mice expressing a truncated form of Cx43 [98]. Although there was no direct connection defined between Cx43 and the directional movement of DCs, it has previously been noted that connexin interacts with c-Src kinase involved in CCL21-directed movement [97][98][99].…”
Section: Directional Migration Of Dendritic Cells Towards Lymphaticsmentioning
confidence: 97%
“…Phosphorylation of oligomeric CCR7 by Src at a tyrosine residue creates a binding site for further signalling molecules containing SH2-domains, which is important for efficient cell migration towards CCL21 [97]. The gap junction protein connexin43 (Cx43) expressed in cDCs has also been identified as a potential player in DC migration towards CCL21 [98]. In vitro studies using bone marrow-derived DCs (BMDCs) from mice with reduced Cx43 expression revealed defective migration towards CCL21.…”
Section: Directional Migration Of Dendritic Cells Towards Lymphaticsmentioning
confidence: 99%
See 1 more Smart Citation
“…The involvement of Cx43 channels in DC-mediated T cell activation is not only limited to its role in facilitating signaling amplification at the IS, but also in DC maturation [53], DC migration to lymph nodes [54] and, as we described below, in promoting the spreading and amplification of antigen cross-presentation pathways.…”
Section: Cx43 Channels Also Impact Dc-mediated T Cell Activation By Amentioning
confidence: 89%
“…During tissue regeneration and following injury, the dedifferentiation, redifferentiation and senescence processes play finely tuned temporal and spatial roles to reverse the loss of tissue in a precise way 35,36 . Cx43, via channel-dependent and -independent functions, has been involved in different phases of tissue regeneration including in controlling acute and chronic inflammation, cell differentiation, migration, proliferation or cellular reprogramming and lately in cellular senescence [22][23][24]37,38 . Results from our lab and others, demonstrated that Cx43 is a target of interest for the treatment of OA in order to stop cartilage degradation and to restore regeneration.…”
Section: Introductionmentioning
confidence: 99%